A Fertile Ground for Ambiguities: Casual Sexual Relationships Among Portuguese Emerging Adults - Luz, Rita; Alvarez, Maria-João; Godinho, Cristina A.; Pereira, Cicero R. (Frontiers in Psychology, 2022)
Casual sexual relationships (CSRs) are frequent relationship experiences in young adulthood that provide opportunities for many to explore sexual relationships and to construct their sexual identity. Empirical research on casual sex is still lacking outside North-American countries, despite evidence pointing to the need to contextualize sexual interactions in their own sociocultural context. In order to better understand casual sexual relationships, these should be examined in with novel samples in other countries where a “hookup culture” as it is described in the North-American university campus is apparently absent. Through a qualitative study, we explored what casual sexual relationships consist of according to the perceptions of Portuguese college students (N = 35). The thematic analysis of eight focus-group interviews resulted in the generation of six themes, three of which are presented here: 1) What CSRs are, regarding features and types of CSRs, 2) Why individuals engage in CSRs, focusing on positive and negative motivations, and 3) What one gets from CSRs, focusing on positive and negative outcomes of CSRs. Our findings showed that Portuguese emerging adults are familiarized with CSRs, particularly with one-night stand, friends with benefits and “curte”/hookup. Sexual interactions associated with other CSRs, such as booty call or fuck buddies were mentioned but rarely associated with a distinctive label and established characteristics. Participants described the CSRs in a partially-overlapping manner presenting some areas of ambiguity, such as with regard to sexual exclusivity and still-unlabeled sexual interactions. CSRs are generally evaluated as positively motivated and mainly beneficial. This study adds to the literature around casual sexual relationships by exploring and describing CSRs in a different sociocultural context, as well as indicating directions for future research in order to better prepare and empower young adults in their sexual and relational trajectories.